Assessing the Relationship Between Training Environment and Training Effectiveness at MAESRK Malaysia Sdn. Bhd. - Mariam, Ibrahim (2011)
This study attempt to evaluate the training effectiveness provided by Maersk Malaysia Sdn. Bhd. This study also identify the influencing factors that effect the training effectiveness, that is training environment. Adopted questioners were used for data collection. Out of 100 participants, 75 respondents returned their questioner, making the response rate of 75 percent. Data was processed and analyse using SPSS. Appropriate data analysis technique were used, both for descriptive and inferential analysis. Findings show that respondents perceived that training environment provided Maersk Malaysia Sdn. Bhd. are good especially on their ability in task involvement. Findings also revealed that training environment is significantly associated and influenced the training effectiveness. Suggestion for future research were made at the section of this study.